Mechanical characterization and induced crystallization in nanocomposites of thermoplastics and carbon nanotubes - Cruz-Chú, Eduardo Roberto; Villegas-Rodríguez, Gonzalo J.; Jäger, Tobias; Valentini, Luca; Pugno, Nicola M.; Gkagkas, Konstantinos; Gräter, Frauke (npj computational materials, 2020)
Nanocomposites built from polymers and carbon nanotubes (CNTs) are a promising class of materials. Computer modeling can provide nanoscale views of the polymer-CNT interface, which are much needed to foster the manufacturing and development of such materials. However, setting up periodic nanocomposite models is a challenging task. Here we propose a computational workflow based on Molecular Dynamics simulations. We demonstrate its capabilities and showcase its applications, focusing on two existing nanocomposite materials: polystyrene (PS) with CNT and polyether ether ketone with CNT. The models provide insights into the polymer crystallization inside CNTs. Furthermore, the PS+CNT nanocomposite models are mechanically tested and able to predict an enhancement in Young’s modulus due to the addition of highly dispersed CNTs. We accompany those results with experimental tests and provide a prediction model based on Dynamic Quantized Fracture Mechanics theory. Our study proposes representative simulations of polymer-CNT nanocomposites as promising tools to guide the rational design of this class of materials.
Gesehen am 14.12.2020